Post-Asean Agreement on Transboundary Haze Pollution: How to Settle the Dispute Settlement? - Fadia Fitriyanti; Yordan Gunawan (Faculty of Law, Hasanuddin University, 2019)
Forest fire happened several times in Indonesia which impacting neighboring countries, such as Malaysia and Singapore. ASEAN tried to